Sedimentology and Geochemistry of the Lower Permian Shanxi Formation Shan 23 Submember Transitional Shale, Eastern Ordos Basin, North China - Gu, Yifan; Li, Xingtao; Qi, Lin; Li, Shuxin; Jiang, Yuqiang; Fu, Yonghong; Yang, Xiaoshuai (Frontiers in Earth Science, 2022)
Shanxi Formation Shan 23 Submember transitional facies shale in Eastern Ordos Basin is characterized by high TOC value, wide distribution, and large single-layer/cumulative thickness. In this study, based on section division of Shan 23 Submember, petrographic, mineralogical, high-resolution geochemical analyses are intergrated to reveal sedimentary environment, detrital influx, paleoclimate, paleosalinity, and paleoredox conditions. Results indicate that Shan 23 Submember is divided into four sections (Shan 23-1, -2, -3 and -4). The upper part of Shan 23-1 section is dominated by bay facies, which is characterized by high TOC value (2.75%-10.96%, avg. 6.98%), low detrital influx proxies (Zr, 97ppm-527ppm, avg. 310ppm; Ti, 1985ppm-7591ppm, avg. 3938ppm), relatively dry paleoclimate condition (CIA*, 41.96-92.58, avg. 75.55; Sr/Cu, 6.23-14.49, avg. 8.87), high paleosalinity proxies (Sr/Ba, 0.39-1.29, avg. 0.62), and relatively anoxic reduction condition (UEF, 0.83-3.00, avg. 1.67; MoEF, 3.95-27.00, avg. 15.56). By comparison, the other three sections are dominated by combination of transitional facies, including barrier island, lagoon, tidal flat and swamp. In this interval, shale is deposited in lagoon facies. The paleoclimate gradually tends to be warm and humid, which result in increasement of chemical weathering intensity. Meanwhile, the detrital influx increases, and the paleoredox condition tends to be oxic. The above conditions are not conducive to the preservation of organic matter in lagoon facies shale.